2013
DOI: 10.35362/rie620588
|View full text |Cite
|
Sign up to set email alerts
|

Corporalidad del «buen estudiante»: representaciones de género, «raza», etnia y clase social en la escuela española

Abstract: El presente artículo es una aproximación socio-antropológica a la construcción del «buen estudiante» en la escuela española a partir de cómo son percibidos los alumnos en función de las clasificaciones realizadas por el profesorado sobre marcadores de género, raciales, étnicos y sociales. Para ello abordamos las condiciones del cuerpo escolarizado que son problematizadas versus las representaciones del mismo consideradas ventajosas para un itinerario educativo de éxito. A partir de la realización del trabajo d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
0
4
2
Order By: Relevance
“…Our results showed that commentators used the "Psychological/Cognitive" theme to construct racial/ethnic difference in relation to players of North African origin. Contrary to our expectations based on previous literature (Chakour & Portillo Fernández, 2018;Olmos Alcaraz & Rubio Gómez, 2013), players we categorized as "North African" were often described in a positive manner, especially in relation to their psychological/cognitive skills, with comments such as "veo un hombre que quiere renovarse, que se está preparando mentalmente" (I see a man who wants to reinvent himself, who is getting ready mentally) or "Brahím ve muy bien a Isco en el segundo palo" (Brahim sees very well Isco at the far post). The numbers also confirmed this trend: they received 16% of the positive commentary in the Psychological/Cognitive theme, with this being a clearly higher percentage than their share in the overall commentary (9%).…”
Section: North African Players and The Psychological/cognitive Themecontrasting
confidence: 99%
See 4 more Smart Citations
“…Our results showed that commentators used the "Psychological/Cognitive" theme to construct racial/ethnic difference in relation to players of North African origin. Contrary to our expectations based on previous literature (Chakour & Portillo Fernández, 2018;Olmos Alcaraz & Rubio Gómez, 2013), players we categorized as "North African" were often described in a positive manner, especially in relation to their psychological/cognitive skills, with comments such as "veo un hombre que quiere renovarse, que se está preparando mentalmente" (I see a man who wants to reinvent himself, who is getting ready mentally) or "Brahím ve muy bien a Isco en el segundo palo" (Brahim sees very well Isco at the far post). The numbers also confirmed this trend: they received 16% of the positive commentary in the Psychological/Cognitive theme, with this being a clearly higher percentage than their share in the overall commentary (9%).…”
Section: North African Players and The Psychological/cognitive Themecontrasting
confidence: 99%
“…It is worth noting that while the pattern that shows how North-African players were portrayed in a positive light referred to several players, the positive comments on the specific theme Psychological/Cognitive referred only to two successful Real Madrid players, Brahim and Benzema, who were described, for instance as “ha sido muy generoso de ceder el balón” (he has been very generous to concede the goal to his colleague), and “tiene madera de lider” (he’s got enough to be a leader), respectively. These findings differ considerably from the everyday discourse about those of North African origin in Spain where they are often described in a negative light and associated with negative cognitive/psychological traits (Cea d’Ancona & Valles Martínez, 2013; Olmos Alcaraz & Rubio Gómez, 2013), which seems to indicate that televised football is able to challenge (instead of reproduce) dominant discourses surrounding racial/ethnic groups. We will return to this in our Discussion.…”
Section: Resultscontrasting
confidence: 80%
See 3 more Smart Citations